LOGO REDESIGN AND PACKAGING OF RUMAH USAHA AL FITRAH - Arif, Sonhaji; Satrio, Putra Uji Deva (Arty: Jurnal Seni Rupa, 2020)
Sidoarjo as a city of Indonesian Small Business Enterprises has a total of 248,306. The large number makes the business climate in Sidoarjo quite competitive. Building a product identity begins with creating a logo as the unique identity of the product. The existence of an identity will make it easier to identify the product on the market. In order to facilitate product identification, product packaging design is also needed. Designing logos and packaging designs is the initial stage to build brand awareness, market awareness of product identity. This study uses a qualitative method by taking a case study of the Rumah Usaha Al Fitrah with its product brand Al Fitrah Kuliner. Using financial results data and interview data to analyze the effect of logos and packaging designs on increasing income. Based on data from the financial reports for the month of June there was an increase of 13.05%, in July there was an increase of 3.69% and in August there was an increase of 19.52%. The results of the interview show several criteria that make consumers interested in the new look of Al Fitrah Kuliner. The attractiveness of logos and packaging designs is seen as quite attractive and seems to be selling quality products. Supported by marketing stands and banners make the promotion of Al Fitrah Kuliner products more professional. The attractiveness of logos, packaging design and promotional media is one of the factors that influence consumer buying interest in products.